2023
DOI: 10.1136/bmjresp-2022-001478
|View full text |Cite
|
Sign up to set email alerts
|

Undiagnosed and ‘overdiagnosed’ COPD using postbronchodilator spirometry in primary healthcare settings: a systematic review and meta-analysis

Abstract: BackgroundDespite chronic obstructive pulmonary disease (COPD) being a major global cause of mortality and hospitalisation, it is often undiagnosed or inaccurately diagnosed in clinical settings.ObjectiveTo systematically synthesise all peer-reviewed papers from primary healthcare settings that have reported data on: (1) undiagnosed COPD, that is, patients with respiratory symptoms and postbronchodilator airflow obstruction consistent with COPD, without a formal clinician’s diagnosis of COPD either documented … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 68 publications
0
2
0
Order By: Relevance
“…The authors demonstrated that COPD was not documented in 14–26% smokers with spirometry-confirmable COPD. In addition, they demonstrated that 25–50% of patients diagnosed with COPD did not have an airflow obstruction 37 . Other studies also revealed that the absence of spirometry is a common cause for under- or over-diagnosis of COPD 38 , 39 .…”
Section: Discussionmentioning
confidence: 99%
“…The authors demonstrated that COPD was not documented in 14–26% smokers with spirometry-confirmable COPD. In addition, they demonstrated that 25–50% of patients diagnosed with COPD did not have an airflow obstruction 37 . Other studies also revealed that the absence of spirometry is a common cause for under- or over-diagnosis of COPD 38 , 39 .…”
Section: Discussionmentioning
confidence: 99%
“…However, these studies do not address and discuss the fact that these patients can have concomitant asthma. Of note, the only difference between the "COPD" population described in the BOREAS trial [4] and a typical population of patients with severe asthma was a smoking history of ≥10 PY (which does not exclude asthma [5]) and a doctor's diagnosis of COPD (which does not exclude the presence of asthma either [12,13]). Our study demonstrates that various types of biologics (and not only one class of biologic) approved for the treatment of asthma [6] can, depending on the respective asthma phenotype, be effective in patients with typical and defined clinical features of both asthma and COPD.…”
Section: Discussionmentioning
confidence: 99%
“…Health professionals are on the frontline, and public health must provide strategies to diagnose and prevent lung disorders and protect and promote health [58], which has been advocated for years [59,60]. This idea gains relevance in a context where spirometry may be underused or, when used, misused [61,62].…”
Section: Xsl • Fomentioning
confidence: 99%